Large‐scale gene expression profiling data for the model moss Physcomitrella patens aid understanding of developmental progression, culture and stress conditions. (9th July 2014) - Hiss, Manuel; Laule, Oliver; Meskauskiene, Rasa M.; Arif, Muhammad A.; Decker, Eva L.; Erxleben, Anika; Frank, Wolfgang; Hanke, Sebastian T.; Lang, Daniel; Martin, Anja; Neu, Christina; Reski, Ralf; et al.
Summary The moss Physcomitrella patens is an important model organism for studying plant evolution, development, physiology and biotechnology. Here we have generated microarray gene expression data covering the principal developmental stages, culture forms and some environmental/stress conditions. Example analyses of developmental stages and growth conditions as well as abiotic stress treatments demonstrate that (i) growth stage is dominant over culture conditions, (ii) liquid culture is not stressful for the plant, (iii) low pH might aid protoplastation by reduced expression of cell wall structure genes, (iv) largely the same gene pool mediates response to dehydration and rehydration, and (v) AP2/EREBP transcription factors play important roles in stress response reactions. With regard to the AP2 gene family, phylogenetic analysis and comparison with Arabidopsis thaliana shows commonalities as well as uniquely expressed family members under drought, light perturbations and protoplastation. Gene expression profiles for P. patens are available for the scientific community via the easy‐to‐use tool at https://www.genevestigator.com. By providing large‐scale expression profiles, the usability of this model organism is further enhanced, for example by enabling selection of control genes for quantitative real‐time PCR. Now, gene expression levels across a broad range of conditions can be accessed online for P. patens.